STRUCTURAL AND QUALITATIVE CHANGES IN ROMANIAS AGRIFOOD FOREIGN TRADE FACING POSTACCESION COMPETITIVENESS - Rusali, Mirela (Economics of Agriculture, 2012)
Within the double context of the disproportions created by the world crisis affecting the economies and of the competitiveness challenges subsequent the EU accession, the paper presents evolution and effects upon the external performances of Romanias agrifood sector and its commercial flows structure. The assessments, including the intraCommunity agri-food trade, highlighted the existing opportunities of the products with expressed export potential and the areas affected by the net imports, by commodity groups aggregated on sections of the C.N.. The calculation of trade relative unit value indices provided the bases for appraisal of the quality of Romanian agricultural trade flows, resulting empiric evidences upon the level of integration of the agricultural trade flows and changes in their terms of trade, on the groups of products of chapters of the C.N..